Patriarchal Culture in Madeline Miller’s Circe - Alif Rafli Rijaal Qasim; Anik Cahyaning Rahayu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. This study is about Patriarchal Culture in Madeline Miller, Circe. The objectives of the study are to identify and explain the forms of patriarchal culture and the effect of patriarchal culture on the main character, Circe. This study utilizes feminist analysis and literary theory approach to unveil the role and influence of patriarchal culture within the novel. Through an in-depth analysis of the main character, Circe, this research reveals how ancient Greek patriarchal culture produce the oppression and subordination of women in society. The findings of this research demonstrate that the novel Circe creatively reinterprets myths and showcases the vulnerability and strength of women that are sometimes overlooked in ancient Greek mythology narratives. The character of Circe is employed to depict women's struggle against patriarchal norms and their quest for self-sovereignty. From the results of analysis, there areetwo formssof patriarchal culture, namely Private Patriarchy and Public Patriarchy. The patriarchal culture that is still considered normal in this fairy tale has a negative impact on the goddess in many ways. Women lose a lot due to the dominance of men over them. Women are devalued by the powerful gods who also put them in a poor position. As a result of this patriarchal culture, the Goddesses are subject to many misconceptions. These gods believe that women are just there to serve their husbands and procreate, as Perse does. The last effect of this patriarchal society is the prevalence of severe physical or psychological violence